The Effect Of Enterprise Risk Management Disclosure, Intellectual Capital Disclosure, Independent Board Of Commissioners, Board Of Director And Audit Committee Towards Firm Value - Bima Cinintya Pratama; Indriana Putri; Maulida Nurul Innayah (Jurnal Manajemen dan Keuangan, 2020)
This study aims to examine the effect of enterprise risk management disclosure, intellectual capital disclosure, board commissioner independent, the board of director and committee audit on firm value proxied using book value. The population in this study are property, real estate, and building construction sector companies listed on the Indonesia Stock Exchange in 2016-2018. The samples of this study are 60 companies with 180 observations listed in Indonesia Stock Exchange selected by using a purposive sampling method. The data analysis method used is multiple regression model. Based on the hypothesis that enterprise risk management disclosure, intellectual capital disclosure, independent board commissioner and audit committee have no significant effect on firm value meanwhile board of directors has a significant effect on firm value.